Inheritance of Alectra resistance in cowpea in genotype B 301 - Singh, B.; Emechebe, A.; Atokple, I. (Wiley, 1993)
Two parasitic weeds, Striga gesnerioides (Willd.) Vatke and Alectra vogelii Benth., cause heavy yield losses in cowpea (Vigna unguiculata (L.) Walp.) throughout the semiarid regions of sub-Saharan Africa. Several sources of resistance have been identified, including B 301, a landrace from Botswana that has shown complete resistance to both striga and alectra. Striga resistance in B 301 is conditioned by a single dominant gene. Our objective was to determine the inheritance of alectra resistance. B 301 was crossed to three susceptible cultivars (IT84S-2246-4, SUVITA-2, and IT82D-849) and F1, F2, and backcross seeds were obtained. The reaction of parental, F1, F2, and backcross plants to alectra infestation was evaluated. Test populations were planted in plastic pots of 13 cm diani. filled with a mixture of sand and soil and ≈800 alectra seeds. The roots of each plant were examined for alectra attachment 10 wk after planting, and the number of resistant and susceptible plants in each population were recorded. All plants of B 301 and backcrosses to B 301 were completely free from alectra. All plants of IT84S-2246-4, SUVITA-2, and IT82D-849 were susceptible. All F2 populations segregated 15 resistant : 1 susceptible, and backcrosses to the susceptible parents segregated 3 resistant : 1 susceptible indicating duplicate dominant gene inheritance. We propose the gene symbols Rav1 and Rav2 (resistance to Alectra vogelii) for this trait.